DNA repair pathways in human multiple myeloma: role in oncogenesis and potential targets for treatment - Gourzones-Dmitriev, Claire; Kassambara, Alboukadel; Sahota, Surinder; Rème, Thierry; Moreaux, Jérôme; Bourquard, Pascal; Hose, Dirk; Pasero, Philippe; Constantinou, Angelos; Klein, Bernard (Cell cycle, 2013)
Every day, cells are faced with thousands of DNA lesions, which have to be repaired to preserve cell survival and function. DNA repair is more or less accurate and could result in genomic instability and cancer. We review here the current knowledge of the links between molecular features, treatment, and DNA repair in multiple myeloma (MM), a disease characterized by the accumulation of malignant plasma cells producing a monoclonal immunoglobulin. Genetic instability and abnormalities are two hallmarks of MM cells and aberrant DNA repair pathways are involved in disease onset, primary translocations in MM cells, and MM progression. Two major drugs currently used to treat MM, the alkylating agent Melphalan and the proteasome inhibitor Bortezomib act directly on DNA repair pathways, which are involved in response to treatment and resistance. A better knowledge of DNA repair pathways in MM could help to target them, thus improving disease treatment.
Gesehen am 24.02.2020